KOMPARASI NILAI TUGAS DAN AFEKTIF DENGAN NILAI ULANGAN MATA PELAJARAN KIMIA - Siti Fatimah Cahyaning Nagari (Universitas Muhammadiyah Semarang, 2017)
The problem in this research was the difference between task and affective score towards test score of grade XI Science in chemistry. This research was an observation research were the researcher made comparison of scores based on scores which were gained without giving special treatments toward the students. The sample of this research was the entire students of grade XI Science in SMAN 2 Wates academic year 2012/2013. The result of this research were the consecutive average task score of class XI IPA 1, XI IPA 2, and XI IPA 3 were 93,00; 88,81; and 86,96; the average of affective score were 78,23; 78,15; and 78,15; and the average test score were 94,50; 94,85; and 90,39. The researcher then computed those data and gained the conclusion that there was significant difference between scores: task and affective score towards test score. The calculation results showedthat there are concrete relationship between task and affective scores towards test score, therefore the teaching learning process should not abandon one or another and should always keep them in good balance to gain the optimum result from students. Keywords:score, test, task, affective.